TRF1 negotiates TTAGGG repeat-associated replication problems by recruiting the BLM helicase and the TPP1/POT1 repressor of ATR signaling - Zimmermann, Michal; Kibe, Tatsuya; Kabir, Shaheen; de Lange, Titia (Genes & development, 2014)
The semiconservative replication of telomeres is facilitated by the shelterin component TRF1. Without TRF1, replication forks stall in the telomeric repeats, leading to ATR kinase signaling upon S-phase progression, fragile metaphase telomeres that resemble the common fragile sites (CFSs), and the association of sister telomeres. In contrast, TRF1 does not contribute significantly to the end protection functions of shelterin. We addressed the mechanism of TRF1 action using mouse conditional knockouts of BLM, TRF1, TPP1, and Rap1 in combination with expression of TRF1 and TIN2 mutants. The data establish that TRF1 binds BLM to facilitate lagging but not leading strand telomeric DNA synthesis. As the template for lagging strand telomeric DNA synthesis is the TTAGGG repeat strand, TRF1-bound BLM is likely required to remove secondary structures formed by these sequences. In addition, the data establish that TRF1 deploys TIN2 and the TPP1/POT1 heterodimers in shelterin to prevent ATR during telomere replication and repress the accompanying sister telomere associations. Thus, TRF1 uses two distinct mechanisms to promote replication of telomeric DNA and circumvent the consequences of replication stress. These data are relevant to the expression of CFSs and provide insights into TIN2, which is compromised in dyskeratosis congenita (DC) and related disorders.
Keywords: shelterin; kultivované buňky; signální transdukce; DNA-Binding Proteins; Protein Binding; replication; mikrosatelitní repetice; DNA Replication; replikace DNA; ATM protein; Signal Transduction; BLM; mutace; serinové proteasy; shelterinový komplex; Serine Proteases; G quadruplex; Microsatellite Repeats; Gene Knockout Techniques; telomere; Cells, Cultured; Enzyme Activation; Shelterin Complex; Mutation; helikasy RecQ; Telomeric Repeat Binding Protein 1; vazba proteinů; genový knockout; aktivace enzymů; Telomere-Binding Proteins; Telomere; telomery; DNA vazebné proteiny; Ataxia Telangiectasia Mutated Proteins; TRF1; proteiny vázající telomery; RecQ Helicases; protein TRF1